2002
DOI: 10.1097/00001756-200205070-00006
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin-induced modulation of dopamine D2 receptors and their function in rat striatum: Counteraction by a NTR1-like receptor antagonist

Abstract: The present study investigated the neurotensin (NT) receptor subtype (NTR) involved in the antagonistic neurotensin modulation of striatal dopamine D2 receptors observed in vitro and in vivo. The NT induced increase of the IC50 values of dopamine (DA) competition for [125I]iodosulpiride binding sites was counteracted by the NTR1-like antagonist SR48692 in rat striatal slices. Intrastriatal perfusion of pergolide induced in the awake rat an inhibition of striatal DA release that was antagonized by NT. This acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…Our electrophysiological data suggest that NT causes acute heterologous desensitization of presynaptic D2R through a PKCand ␤-arr1-dependent mechanism. Numerous reports have shown that NT can also negatively regulate postsynaptic D2R function in the striatum and other brain regions (55,(63)(64)(65). As suggested by our present results, it is possible that NT regulates pre-and postsynaptic D2Rs via a similar heterologous desensitization mechanism, but with different magnitudes and time courses.…”
Section: Discussionsupporting
confidence: 67%
“…Our electrophysiological data suggest that NT causes acute heterologous desensitization of presynaptic D2R through a PKCand ␤-arr1-dependent mechanism. Numerous reports have shown that NT can also negatively regulate postsynaptic D2R function in the striatum and other brain regions (55,(63)(64)(65). As suggested by our present results, it is possible that NT regulates pre-and postsynaptic D2Rs via a similar heterologous desensitization mechanism, but with different magnitudes and time courses.…”
Section: Discussionsupporting
confidence: 67%
“…Recent work also indicates that there are extensive NT inputs to the VTA [178], and AMP-evoked NT release in this region could also modulate local neurotransmitter release, although such release has not been demonstrated. NT activation of dopamine neurons would seem to be unlikely to be involved in augmenting dopamine release since AMP releases dopamine from non-vesicular stores by promoting reverse transport through the dopamine transporter [179], although as mentioned above NT could augment AMP stimulation of dopamine release through attenuation of D 2 autoreceptor signaling [169,170,180].…”
Section: Nt Modulation Of Psychostimulant Responsesmentioning
confidence: 97%
“…62,2005 Review Article 1953 NMDA receptor signaling, suggesting that NT is released from D 1 -positive neurons [167,168]. NT could influence AMP-stimulated outflow of dopamine through a dampening of D 2 receptor-mediated autoinhibition [169], since this process reportedly modulates AMPevoked dopamine release [170]. NT microinjection in the striatum also increases glutamate release [100,171], suggesting that local NT release could augment glutamate signaling, as argued above for APD responses.…”
Section: Nt Modulation Of Psychostimulant Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of Ntsr1-DA receptor interaction varies with cells and brain regions. For example, in striatal neurons, NT suppresses presynaptic D 2 -like autoreceptors, which results in an increased level of extracellular DA (Diaz-Cabiale et al, 2002;Ferraro et al, 1997). Notably, Ntsr1 decreases the agonist-binding affinity of D 2 -like receptors via allosteric Ntsr1-D 2 -like receptor interactions (Diaz-Cabiale et al, 2002;von Euler et al, 1989).…”
Section: Introductionmentioning
confidence: 99%